Reproducibility of Neurochemical Profile Quantification in Pregenual Cingulate, Anterior Midcingulate, and Bilateral Posterior Insular Subdivisions Measured at 3 Tesla - de Matos, Nuno M. P.; Meier, Lukas; Wyss, Michael; Meier, Dieter; Gutzeit, Andreas; Ettlin, Dominik A.; Brügger, Mike (Frontiers in Human Neuroscience, 2016)
Current report assessed measurement reproducibility and reliability of magnetic resonance spectroscopy (1H-MRS) at 3 Tesla in left and right posterior insular, pregenual and anterior midcingulate subdivisions. 10 healthy male volunteers aged 20 to 30 years were tested on four different days, of which 9 were included in the data analysis. Intra- and inter-subject variability of myo-Inositol (mI), Creatine (Cre), Glutamate (glu), total-Choline (tCho), total-N-acetylaspartate (tNAA) and combined Glutamine-Glutamate (Glx) were calculated considering the influence of movement parameters, age, daytime of measurements and tissue composition. Overall mean intra-subject variability revealed small mean coefficients of variation (CV) across the four regions: 5.3% in aMCC, 6.6% in pgACC, 7.3% in pIL and 8.2% in pIR. For all neurochemicals combined, mean inter-subject variability demonstrated mean CVs of 9.05% (aMCC), 8.84% (pgACC), 10.00% (pIL) and 10.55% (pIR). Head movement, tissue composition and day time revealed no significant explanatory variance contribution suggesting a negligible influence on data. A strong correlation between Cramer-Rao Lower Bounds (CRLB; a measure of fitting errors) and the mean intra-subject CV (r=0.799, p<0.001) outlined the importance of low CRLB in order to obtain robust and finally meaningful 1H-MRS measures. The present findings confirm 1H-MRS as a reliable tool to measure brain neurochemistry in small subregions of the human brain.